Sistem Pakar Mendiagnosa Penyakit Sampar Menggunakan Metode Hybrid Case Based - Nuraida Br Ginting; Garuda Ginting; Natalia Silalahi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Sampar, also known as a pest or black death or plague, is a bacterial infection of Yersinia pestis (Y.pestis), where the disease is actually a zoonotic disease, which is an animal disease transmitted by humans. This disease is caused by the bacterium yersinia pestis which lives on fleas, where these fleas live in rodents (especially mice). Fleas spread disease when sucking rat or human blood. This disease is also called plague due to black patches found in the skin of the patient at the beginning of the outbreak. This pestilence was once an epidemic in 1347-1351 in Europe and other regions and killed approximately 75 million people in the world. This disease in Indonesia is still under monitoring and is one of the infectious diseases in the outbreak law that must be reported to the health office. According to WHO this disease is one of the deadly infectious diseases after infection and patients can die within 24 hours. So that people are more careful with this disease so that they are not exposed to pestilence. Because many people do not recognize the transmission of Yersinia pestis bacterial infections and do not know the symptoms that arise from pestilence. then a system for pestilence is created which aims to better diagnose early onset of this pestilence. The method applied in expert systems and one of them is a case based hybrid. Hybrid case based is one of the mathematical theories for proof based on belief functions and plausible reasoning, which is used to combine separate pieces of information or evidence to calculate a probability of an event (Arthur P.Dempster and Glen Shafer)